2012
DOI: 10.1088/0004-637x/747/1/70
|View full text |Cite
|
Sign up to set email alerts
|

A Revised View of the Transient Radio Sky

Abstract: We report on a re-analysis of archival data from the Very Large Array for a sample of 10 long-duration radio transients reported by Bower and others. These transients have an implied all-sky rate that would make them the most common radio transient in the sky and yet most have no quiescent counterparts at other wavelengths and therefore no known progenitor (other than Galactic neutron stars). We find that more than half of these transients are due to rare data artifacts. The remaining sources have lower signal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
134
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(143 citation statements)
references
References 61 publications
8
134
1
Order By: Relevance
“…Our detection indicates a transient surface density that is more strict than the limit from Bower et al (2007), even considering the factor of two decrease suggested by Frail et al (2011). However, the frequency range in Figure 9 sults with similar flux sensitivity.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Our detection indicates a transient surface density that is more strict than the limit from Bower et al (2007), even considering the factor of two decrease suggested by Frail et al (2011). However, the frequency range in Figure 9 sults with similar flux sensitivity.…”
Section: Discussionsupporting
confidence: 46%
“…All published limits have been scaled to represent the surface density at 95% confidence. The Bower et al (2007) results have also been adjusted to reflect the recent reanalysis by Frail et al (2011). For completeness, we note the non-detection limit from Lazio et al (2010) of Σ < 10 −7 with flux sensitivity >2.5 kJy at 74 MHz.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, radio afterglows have been already detected for four sGRBs(e.g., Fong et al 2015) and they will be detectable counterparts of GW merger events (Feng et al 2014). Recent observations suggest that the radio transient sky is far quieter compared to the optical one, so we expect far fewer false positives by a factor of a hundred or more depending on the sky location than in the optical-IR (e.g., Frail et al 2012;Mooley et al 2013Mooley et al , 2016. This paper focuses on strategies for detecting and identifying, following the detection of a GW event, two different radio post-merger counterparts: (i) the longer duration radio remnants that may last from months to years and (ii) the faster ultrarelativistic radio afterglow components that last weeks to months (Nakar & Piran 2011;Piran et al 2013;Margalit & Piran 2015).…”
Section: Introductionmentioning
confidence: 98%
“…No single map contributes more than this, which implies that no single observation dominates the observed excess. This rules out the kinds of brief instrumental systematics identified by Frail et al (2012) in previous radio transient surveys.…”
Section: Candidate Objectmentioning
confidence: 60%